High-grade glioma in very young children: a rare and particular patient population - El-Ayadi, Moatasem; Sturm, Dominik (OncoTarget, 2017)
Abstract: In the past years, pediatric high-grade gliomas (HGG) have been the focus of several research articles and reviews, given the recent discoveries on the genetic and molecular levels pointing out a clinico-biological uniqueness of the pediatric population compared to their adult counterparts with HGG. On the other hand, there are only scarce data about HGG in very young children (below 3 years of age at diagnosis) due to their relatively low incidence. However, the few available data suggest further distinction of this very rare subgroup from older children and adults at several levels including their molecular and biological characteristics, their treatment management, as well as their outcome. This review summarizes and discusses the current available knowledge on the epidemiological, neuropathological, genetic and molecular data of this subpopulation. We discuss these findings and differences compared to older patients suffering from the same histologic disease. In addition, we highlight the particular clinical and neuro-radiological findings in this specific subgroup of patients as well as their current management approaches and treatment outcomes.